AWARENESS, KNOWLEDGE AND ATTITUDE ABOUT DENGUE AMONG SOCIETY - P. J., PATIL; V. S., PATIL; R. D., CHAUDHARI; J. S., MALU (International Journal of Current Pharmaceutical Research, 2020)
Objective: The survey about dengue was carried out to gather the information about dengue fever, create awareness among the people. To determined the index of knowledge, attitude and awareness among the surveyed population about dengue. Methods: The questionnaire was prepared under the guidance of a pharmacologist. Pilot study was conducted among ten nos. of the population prior actual study. Questionnaire was revised and finalized according to an input of the pilot study. This questionnaire presented to the hundred peoples of different age group. Method involves face to face interview and seeking answers for different questions. Responses were recorded for further analysis and interpretation. Responses were sorted and analyzed. Different questions were categorized into the domain of awareness, knowledge and attitude. Data was presented in the form of graphs. Results: Percentage of awareness, knowledge and attitude found to be 59, 44, 52 respectively. It is observed that three parameters are almost in the range of fifty percent. Precautions plays vital role in prevention of Dengue. Conclusion: it is concluded that there is scope for improvement for creating awareness, knowledge and attitude among the surveyed population as representative of the general population. This may help to overcome the risk of this communicable and deadly disease.